Pengaruh Partisipasi Anggaran Terhadap Kinerja dan Budgetary Slack Dengan Locus Of Control Sebagai Variabel Pemoderasi(Studi Empiris pada Hotel Berbintang di Surakarta dan Solo Baru) - Erawati, Herlina (2016)
This research purpose to analyze: 1) the influence of budget participation to performance, 2) the influence of budget participation to budgetary slack, 3) the influence of locus of control as moderating the correlation between budget participation to performance, 4) the influence of locus of control as moderating the correlation between budget participation to budgetary slack. This research population was manager at eight star hotels in Surakarta dan Solo Baru. Sampel determined by using purposive sampling method. This research has 56 respondents from eight star hotels. In this research, hypothesis tested by using multipple linier regression. This research shows that budget participation have influence to performance, this matter was shown with tcount value equal to 2,530 with probability equal to 0,014 (p < 0,05). Budget participation have influence to budgetary slack, this matter was shown with tcount value equal to 2,337 with probability equal to 0,023 (p < 0,05). Locus of control has moderating the correlation between budget participation to performance, this matter was shown with tcount value equal to -3,012 with probability equal to 0,004 (p < 0,05). Locus of control has moderating the correlation between budget participation to budgetary slack, his matter was shown with tcount value equal to -2,013 with probability equal to 0,049 (p < 0,05).